ONLINE LEARNING INTERACTION OF MATHEMATICS TEACHER IN JUNIOR HIGH SCHOOL: A SURVEY IN THE COVID-19 PANDEMIC - Ahmad Ahmad; Zulkifley Mohamed; Eka Setyaningsih; Chumaedi Sugihandardji (IKIP Siliwangi and I-MES, 2021)
This study aims to determine the online learning interactions carried out by junior high school teachers in the classroom during the COVID-19 pandemic. The quantitative using survey was used as a research methodology. 141 Mathematic Teachers was selected as the subject of this research. A questionnaire of classroom interaction practice in an online class was used as a data collection technique. The result found that mathematic teachers’ interaction activity in online courses has a different level. The interaction process that mathematic teachers use is in preparing the students to join an online course and leading the discussion with the mean of 4.2 and 4.3. In contrast, the lowest interaction happens in interaction in giving feedback and interaction in closing activity with an average of 2.5. the research also found that 78.70% of mathematic teachers always provide direction to the students in starting the online class. 40.30% of them never ask students to correct incorrect assignments during online learning.